The Tunisian School of Jurisprudence and the Theory of its Moderate Line - Al-Houssaini, Abdennabi Mohammad Esgheir (Journal of Islamic Sciences, 2025)
This research aims to demonstrate the intellectual and methodological specificity of the Tunisian School of jurisprudence, characterized by moderation, balance, and flexibility. In other words, it attempts to show how far the Tunisian School of jurisprudence was from fanaticism and blind imitation, on the one hand, and how open to reason and logic, and operating within the framework of the objectives of religion, on the other. In addition, it aims to show how capable it was of overcoming hardships and keeping pace with development. Since our research is demonstrative and deductive in nature, it is based on a set of appropriate and effective scientific research methods. The most important of these is the historical-inductive method, which allows us to extrapolate historical events and facts, as well as the analytic-critical method, which enables us to critically analyze the subjects and data of our research. As for the argumentative approach, it is used effectively in reasoning processes. This work is composed of three chapters and a number of sub-chapters to support our thesis. The first addresses the emergence of the Tunisian School of jurisprudence, including some sub-chapters, such as the influence of Malik and Medina on Kairouan and the Kairouanites, the role of Tunis in the emergence of the Kairouan School of jurisprudence, and the circumstances of the transfer of the scientific foundations of Maliki jurisprudence from Kairouan to Tunis. While the second chapter deals with the theory of moderation of the Tunisian School of jurisprudence, and it contains a number of sub-chapters, such as the repudiation to Kharijite extremists by the early Kairouan society, the resistance of the Sanhaja state against the Fatimid call, and the rejection of the Wahhabi call by Tunisian scholars. As for the third and most important chapter, it encompasses practical work on a group of the most distinguished scholars of the Tunisian School of jurisprudence, to each of whom we have devoted a special subchapter in order to support and strengthen our thesis. Thus, our research achieved a number of results, including demonstrating the moderation and flexibility of the Tunisian School of jurisprudence, showing that it is the fruit of a long Maliki jurisprudential process that began in Medina and continued on to Kairouan and then to Tunis. Perhaps the most important result is the likeliness and capacity of the Tunisian School of jurisprudence to evolve and produce pioneering innovations like financial punishment, thanks to reason and logic.
Keywords: Tunisia; Jurisprudence; Imitation; Reason; Flexibility